2020
DOI: 10.3389/fimmu.2020.00707
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Kinase Myasthenia Gravis

Abstract: Thirty to fifty percent of patients with acetylcholine receptor (AChR) antibody (Ab)negative myasthenia gravis (MG) have Abs to muscle specific kinase (MuSK) and are referred to as having MuSK-MG. MuSK is a 100 kD single-pass post-synaptic transmembrane receptor tyrosine kinase crucial to the development and maintenance of the neuromuscular junction. The Abs in MuSK-MG are predominantly of the IgG4 immunoglobulin subclass. MuSK-MG differs from AChR-MG, in exhibiting more focal muscle involvement, including nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 155 publications
0
21
0
Order By: Relevance
“…Unfortunately, to date, there are almost no disease-specific therapies for neuroimmunological diseases. However, in vitro (cell cultures) and in vivo (animal, brain pathology and clinical) studies have suggested the presence of different pathophysiological mechanisms in patients with different antibody types and subtypes ( 152 , 153 ). These findings suggest that special treatment requirements may apply to neuroimmunological diseases with different antibody subtypes, including patients with dominant IgG4 antibodies, and indeed IgG4-AID have a unique response pattern to conventional therapies for autoimmune diseases.…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…Unfortunately, to date, there are almost no disease-specific therapies for neuroimmunological diseases. However, in vitro (cell cultures) and in vivo (animal, brain pathology and clinical) studies have suggested the presence of different pathophysiological mechanisms in patients with different antibody types and subtypes ( 152 , 153 ). These findings suggest that special treatment requirements may apply to neuroimmunological diseases with different antibody subtypes, including patients with dominant IgG4 antibodies, and indeed IgG4-AID have a unique response pattern to conventional therapies for autoimmune diseases.…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…Antibody testing has a crucial role for clinical diagnosis confirmation and treatment. Majority of MG patients (around 80–85%) develop Abs against the acetylcholine receptors (AChR; AChR MG), whereas muscle-specific kinase Abs (MuSK; MuSK MG) are detected in 1–10% patients, depending on detection techniques used and the differences between the source population ( 5 , 8 , 9 ). Interestingly, Abs are not detected in around 1–15% of MG patients [that is, negative for AChR, and MuSK Abs with current gold standard methods; seronegative MG (SNMG)] ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different MG subgroups have been proposed based on the age of onset [early onset MG (EOMG; onset ≤ 50 years of age); late onset MG (LOMG; onset > 50 years of age)], antibody profile [acetylcholine receptor antibody seropositive (AChR+), muscle specific tyrosine kinase antibody seropositive (MuSK+)], weakness distribution (OMG vs. GMG) and thymic abnormalities [ 1 , 2 ]. Different subgroups reflect important implications in both prognosis and therapeutic management [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%